On the incidence graph of circular spaces - Sorgun, Sezer; Ertaş, Ali Gökhan; Günaltılı, İbrahim (Electronic Journal of Graph Theory and Applications (EJGTA), 2024)
A configuration of the triple (P,L,I) is an incidence relation which has the properties "any two points are incident with at most one line" and "any two lines are incident with at most one point". In projective geometry, bipartite graphs can be used as an incidence model between the points and lines of a configuration. The graphs associated with a space are a good tool for understanding the topological and geometric properties of space in abstract systems. In this paper we focus on the incidence graph of circular space and obtain its properties in terms of some pure graph invariants. We also characterize it in terms of the graphs associated with other spaces in the literature.